Effects of Moringa oleifera Leaf Extracts on Lipid Profile of Rats: A Meta-Analysis and Systematic Review - Lacorte, Laarni Hannah; Robles, Jayson Harbey; Panganiban, Cathleen; Cajano, John Vince; Santos, Jose Bryan; Ortiz, Celjan Kyle; Gumban, MA Theresa; Sancho, Joanne Emille; Nas, John Sylvester (Asian Journal of Biological and Life Sciences)
Moringa oleifera (MO) has long been studied for its anti-obesity potential and its various effects on the lipid profile. However, the result of the basic researches done in rats appears to be imprecise, which may be due to the differences in the solvent extraction, dosing, and duration of administration of the extract. This paper evaluated the effects of different solvent extraction, dosing, and duration of administration of MO extracts on the lipid profile of rats, namely total cholesterol (TC), triglyceride (TG), low-density lipoproteins (LDL), and high-density lipoproteins (HDL). The articles used in this study were collected from various reputable indexing platforms. Meta-analysis was performed to compare the different treatments in the lipid profile of the rats through one-way analysis of variance (ANOVA) with Tukey’s test, one-way ANOVA on ranks with Mann-Whitney test, and student t-test. Results show no significant difference (p < 0.05) in the rats’ lipid profile after treatment of different MO extracts, suggesting that regardless of the MO solvent used results in a similar effect on the lipid profile of rats. However, the disparity of the effects on the lipid profile may be attributed to the dosing and duration of administration. We hypothesized that the level, bioavailability, and mechanism of action of certain phytochemicals present in MO extracts such as flavonoids, phenols, anthraquinones, terpenes, phenolic acids, flavones, terpenoids, and steroids might have also contributed to these differences. Hence, isolation of bioactive compounds from MO and testing their effects on different lipid-associated enzymes may elucidate the actual impact of MO in the lipid profile.
Keywords: Bioactive compounds; Leaf extract; Lipid profile; Moringa oleifera; Phytochemicals; Rats